Impact of Social Networks on Entrepreneurial Innovation and Business Performance in SMEs - Binh Le; Ngoc Tien Nguyen (Emerging Science Journal, 2025)
This study utilized the panel data of Small and Medium Enterprises Surveys (SMES: 2009-2015) and used the two-way fixed effects model to assess the relative association between social networks and entrepreneurial innovation and business performance in Vietnam. The results supported the hypotheses that social networks are positively associated with the likelihood of entrepreneurial innovation and business performance from the perspective of micro, small, and medium enterprises. A 1% increase in social networks was associated with an increase of 2.8 percentage points in incremental product innovation and 1.5 percentage points in process innovation. The more extensive social networks also helped enterprises perform their business better by increasing their real revenue, real profit, and rate of return on assets. In addition to contributing to the well documented literature of the role of social networks in entrepreneurial innovation and business performance, the novelty of the research was highlighting the relationship varied by ownership, organizational structure, and location. The local business association membership was also matter for entrepreneurial innovation and firm performance in the Vietnamese SMEs. The results were, therefore, informative for policymakers and SME entrepreneurs.